Esthetic and endosurgical management of turner′s hypoplasia; a sequlae of trauma to developing tooth germ - Bhushan B; Garg S; Sharma D; Jain M (Wolters Kluwer Medknow Publications, 2008)
Turner′s hypoplasia usually manifests as a portion of missing or diminished enamel, generally affecting one or more permanent teeth in the oral cavity. A case report of 8 year old girl who met with trauma at 2 years of age leading to primary incisors being knocked out, reported after 6 years with complaint of pain and discharge in her anterior malformed teeth is discussed in this article. The permanent incisors erupted with dilacerated crown, root malformations and missing enamel. Further, patient developed sinus, lateral root pathology, tooth mobility and malocclusion in relation to affected teeth which were managed by esthetic, functional, endodontic and surgical procedure. Root canal treatment along with palatal contouring and esthetic restoration by light cure composite was performed on the tooth with crown dilaceration and sinus, where as surgical management was considered for the tooth with root malformation.